Rastros no meio digital: o consumo e uso cultural das redes sociais pelos jovens de Muquém a partir do Instagram Stories - Abreu, Maria Evilene de Sousa (2023)
This work researches the consumption and cultural use of social networks by eleven young people from the rural community of Muquém based on their traces in digital environments, specifically on the Instagram Stories platform. Besides the material collected on Instagram Stories, the study considers young people's narratives outside the social network, aiming to understand how they interact and communicate with each other and the world around them, in other words, what communication processes are mediated by technologies. This research is based on the theoretical contribution of the authors Rincón (2018), Jesus Martín-Barbero (1987; 2000), Wolton (2023) and Canclini (1990; 2021), in order to understand the communication phenomenon beyond digital media and technologies. From an ethnographic perspective (GREEN; DIXON; ZAHARLIC, 2005), including the autoethnography (VERGUEIRO, 2015; GAMA, 2020) and ethnography for the Internet (HINE, 2004; 2015), the study considered the knowledge and information that comes from historical, cultural and social experiences of young people in order to grasp the universe of meanings of the young narrators from the research. Even with precarious access to the internet, it is a generation of young people with more schooling and opportunities. During the Covid-19 pandemic, there was a significant increase in the use of the internet and digital media, as well as the ways in which people socialize, interact and communicate in the world have changed. It was no different in the Muquém community. Residents, mainly youngsters, have constant access to digital media. Studying, working, playing games, listening to music, watching movies and TV shows, talking to friends and even parents have all been done through apps and virtual platforms, significantly changing the community's day life routine.